Dinamika Parameter Mikrofisis Hujan Es berbasis Satelit dan Data Model Reanalisis - Carundyatama, Daniar Ihza; Novitarini, Putu Widya; Hakim, Muhammad Zaidan; Winarto, Hari; Kristianto, Aries (Universitas Pendidikan Ganesha, 2025)
Hail events result from atmospheric dynamic processes, including a low freezing layer, strong downdrafts, and the growth of convective clouds. This study describes the microphysical dynamic conditions during the hail event in Batu City, East Java Province, on November 2, 2024. Microphysical analysis was conducted using observations, satellite data, and ERA5 ECMWF reanalysis data. The microphysical reanalysis data reveal dynamics in vertical, horizontal dimensions and time series during the formation to dissipation phases. Radiosonde observation data were used for atmospheric stability analysis. Additionally, IR imagery showed increased convective activity with very low temperatures reaching -75°C. The low boundary layer height and increased total cloud column ice indicate a significant concentration of ice particles. The moderate CAPE value of 1300 J/kg indicates sufficient energy potential for convection, while the low CIN value of 50 J/kg facilitates upward air movement to form clouds. The low LFC height and high EL further strengthen the indication that convection can develop vertically into the upper troposphere, allowing for the formation of intense hail.